DIW Berlin economic forecast: Forecast ranges from cloudy to bright - Timm Bönke; Geraldine Dany-Knedlik; Guido Baldi; Hella Engerer; Pia Hüttl; Konstantin Kholodilin; Frederik Kurcz; Theresa Neef; Laura Pagenhardt; Werner Röger; Marie Rullière; Jan-Christopher Scherer; et al. (DIW Weekly Report, 2023)
The recovery of the German economy is becoming an exercise in patience. In the third quarter of 2023 the economy fared worse than expected, in particular because private households continued to spend their money conservatively despite climbing wages and falling inflation. Both private consumption and overall economic output even declined slightly. Now the next challenge has arrived: In November 2023, the German Federal Constitutional Court ruled that the reallocation of unused coronavirus pandemic funds to the Klima- und Transformationsfonds (KTF) is unconstitutional. This ruling has far-reaching consequences for public budget and thus also for economic development in Germany. This forecast is based on the assumption that funds will be cut, particularly for investments, with the necessary cutbacks amounting to around 19 billion euros in 2024 and 2025 each, eleven billion euros in 2026, and three billion euros in 2027. There is also considerable uncertainty surrounding the reorganization of the budget. The assumed cuts to public funds underlying this report were made before a budget deal was reached on December 13, but correspond in structure and scale to the consolidation proposals of the government. The Federal Government quickly suspended the debt brake again for 2023 by declaring a state of emergency. In the 2024 federal budget, the Federal Government primarily agreed to around twelve billion euros' worth of cuts to subsidy programs and corporate compensation from the KTF and a minor carbon price increase of five euros. The 2024 budget also preserves the EEG surcharge and the heating program as part of the Building Energy Act. A further 17 billion euros are to be generated through cuts to the core budget. DIW Berlin expects a 0.3 percent decline in economic output for 2023. The German economy is expected to grow by 0.6 percent in 2024 and by 1.0 percent in 2025. Thus, the economic recovery will be much slower than was expected according to the DIW Berlin autumn forecast. The cancellation of public funds and the uncertainty resulting from the Federal Constitutional Court's ruling will reduce growth by 0.3 percentage points in 2024 alone. Overall, the forecast was downgraded by 0.6 percentage points compared to autumn, as, in addition to the ruling and its consequences for investment activity, private consumption is struggling to find momentum. The global economy remains robust. With the exception of China, both advanced and emerging economies have recently experienced solid growth. Economic output is still weak in the euro area and the United Kingdom. However, falling inflation rates will increasingly strengthen real wages in these countries, which should support purchasing power in 2024. Due to the gradual recovery in Europe as well as China and a cooling economy in the United States, global economic growth will be somewhat lower in 2024 at 3.7 percent.
Keywords: E17; D31; E66; 330; Nowcast; income distribution; inequality